The interaction effect of auditor industry specialisation and board governance on financial reporting timeliness: evidence from the UAE - Al-Muzaiqer, Mohammed Ali Hussein; Ahmad, Maslina; Abdul Hamid, Fatima (Emerald Publishing Limited, 2023)
This study investigates how the timeliness of financial reporting by listed companies in the United Arab Emirates (UAE) is influenced by the interaction effect between industry-specialist auditors and board governance. The Emirati capital markets–the Abu Dhabi Securities Exchange (ADX) and the Dubai Financial Market (DFM)–were used to obtain the data, which covered the seven-year period between 2011 and 2017. In total, 385 observations were obtained. Descriptive statistics and multiple regression were the principal statistical tests employed using the panel data method. The results of the direct effect tests reveal that board independence and industry-specialist auditors have no significant influence on financial reporting timeliness. Nevertheless, the results also show that the timeliness of financial reporting by listed companies in the UAE is influenced by the interaction effect between auditors’ industry specialisation and the governance of firm boards. More specifically, the results reveal that financial reporting timeliness is positively associated with board independence for companies audited by industry-specialist auditors. This finding is consistent with the notion that industry-specialist auditors complement the role of effective board governance. The main contribution of this study to the overall body of research is the concept that having independent directors is associated with improved reporting timeliness because financial reports are monitored with greater efficiency by industry–specialist auditors. This study provides evidence for the interaction effect between internal and external governance mechanisms on financial reporting quality, which has not been the focus of prior studies on financial reporting quality.